PENANGANAN KASUS NAMA PENANGGUNG PEMINJAMAN KREDIT PADA LEMBAGA PERKREDITAN DESA ADAT SEMANA, KABUPATEN BADUNG - I Kadek Doni Erry Gunawan; Anak Agung Kt Sudiana (Jurnal Hukum Mahasiswa, 2023)
The Village Credit Institution is a financial institution under the auspices of the Traditional Village. Lending is a strategic function of the Village Credit Institution. In the credit loan agreement at the Semana Traditional Village Credit Institution, Badung Regency, it is mandatory to use the name of the guarantor where the name of the guarantor comes from 1 family registered on the Family Card. The use of the name of the guarantor in applying for credit aims to prevent bad credit, in its implementation in several cases cases of bad credit are still found. This study uses empirical legal research methods. Based on the research that has been carried out, it can be explained that the use of the name of the guarantor in lending credit to the Semana Traditional Village Credit Institution, Badung Regency has not been effective. There are legal factors and factorsnon law that affects the effectiveness of using the name of the guarantor in lending credit to the Semana Traditional Village Credit Institution, Badung Regency so that efforts need to be implemented to overcome these factors.